Personalised written consultation summaries for patients: An 'up-close, in-depth, inside-out' exploration of a rheumatologist's patient-centred strategy. Issue 7 (July 2022) - Tvedten, Olav Gjønnes; Croker, Anne; Lawrence, Marina; Williams, Katrina; Perry, Narelle; Croker, Jim
Highlights: Patient-centred strategies are an important aspect of rheumatology consultations. Providing personalised written consultation summaries for patients is one strategy. Collaborative enquiry explored this strategy with two patients in the research team. Developed with and for patients, summaries provide an enduring reference point. Relevant for health literacy, personal information management, medication adherence. Abstract: Objective: The importance of ensuring that patients understand and remember information from rheumatology consultations is well recognised. However, literature focuses on 'one-size-fits-all' information resources. In this qualitative study our 'upclose, in-depth, inside-out' exploration sought to understand the personalised written consultation summary, a rheumatologist's patient-centred strategy developed through ongoing reflection. Methods: A research team of a rheumatologist, practice nurse, two patients, registrar and researcher used a participatory research approach, collaborative inquiry Semistructured interviews were undertaken with 29 patients. Data analysis was dialogical and iterative, moving from descriptive to conceptual. Results: Implicit within the personalised written consultation summary were domains and actions of: INVOLVEMENT in the process (contributing to the content, clarifying and negotiating the content, being present as it is written), CONTINUITY of information (taking the summary, sharing it with others, storing it at home) and SECURITY for ongoing management (owning the summary, being reminded about management plans, having a basis for re-checking). Conclusion: Aligned with the findings are patient-centred intentions for health literacy, personal health information management and medication adherence. The second highlights an important theoretical basis for patient-centred rheumatology strategies beyond consultations. Practice implications: A model and reflective questions are presented to inform ongoing reflections about patient-centred information strategies.